Penerapan Project-Based Learning pada Mata Pelajaran Dasar Listrik Elektronika - Rizki Karima; Sukardi Sukardi (Jurnal Pendidikan Teknik Elektro, 2023)
This study aims to increase the activeness of students in the basic subjects of electronic electricity in class XI of SMKS Muhammadiyah 1 Padang by using the PjBL learning method. This study uses quantitative descriptive research methods by means of survey method research. The subject of this study was a grade XI TITL student at SMKS Muhammadiyah 1 Padangi in the even semester of the 2022/2023 academic year consisting of 9 students. The data collection method uses learning tool validity questionnaires validated by media experts and material experts and practicality questionnaires filled out by students and teachers. The results of the study obtained the validity of media and materials with valid categorization, where the media learning tools with the application of the PjBL method are feasible to use. The results of teacher practicality research using PjBL are categorized as good. The results of student practicality research using PjBL are also good. Thus, the application of the PjBL learning method in basic electronic electricity subjects can increase student activeness and is feasible to be applied in class XI of SMKS Muhammadiyah 1 Padang.